2021
DOI: 10.3390/v13112223
|View full text |Cite|
|
Sign up to set email alerts
|

Hypovitaminosis D Is Associated with Higher Levels of Inflammatory Cytokines and with HAM/TSP in HTLV-Infected Patients

Abstract: Recent studies have shown the effects of vitamin D on host response to infectious diseases. Some studies detected a high prevalence of hypovitaminosis D in HIV-infected patients, but scarce information exists for HTLV-1 infection. We conducted a cross-sectional study to evaluate the frequency of hypovitaminosis D in HTLV-1 patients and its relationship with their immune response in HTLV-infected patients and in age- and gender-matched controls at a Brazilian rehabilitation hospital. We compared vitamin D, inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…There is considerable research interest in the role of vitamin D as an immunomodulator in HIV, as it decreases inflammation, decreases bone marker turnover and improves the treatment of secondary hyperparathyroidism [ 83 , 84 ]. Furthermore, the decrease in vitamin D plasma levels was also found to be associated with an increase in the production of cytokines [ 85 ]. Several studies [ 86 , 87 ] have identified a reduction in parathyroid hormone (PTH) or bone turnover markers.…”
Section: Calcium and Vitamin Dmentioning
confidence: 99%
“…There is considerable research interest in the role of vitamin D as an immunomodulator in HIV, as it decreases inflammation, decreases bone marker turnover and improves the treatment of secondary hyperparathyroidism [ 83 , 84 ]. Furthermore, the decrease in vitamin D plasma levels was also found to be associated with an increase in the production of cytokines [ 85 ]. Several studies [ 86 , 87 ] have identified a reduction in parathyroid hormone (PTH) or bone turnover markers.…”
Section: Calcium and Vitamin Dmentioning
confidence: 99%
“…In the original publication [ 1 ], there was a mistake in the Figure 1 labels of the vertical axis, which were not properly formatted: The values in the vertical axis were shown as RAL1900, due to an error in the figure’s uploading process. The correct values are 0, 20, 40, 60, 80 and 100.…”
Section: Error In Figurementioning
confidence: 99%
“…In the original publication [1], there was a mistake in the Figure 1 Error in Figure 1 In the original publication, there was a mistake in Figure 1 as published.…”
Section: Error In Figurementioning
confidence: 99%